Gamification narrative design as a predictor for mobile fitness app user persistent usage intentions: a goal priming perspective. Issue 10 (26th November 2021) - Li, Manning; Wang, Yancheng; Wu, Yueming; Liu, Hanchen
ABSTRACT: Many users fail to stick to the use of mobile fitness apps. As a key element of gamification mechanisms, effective gamification narrative design has the potential to draw the users in and motivates them to develop stronger motivations to achieve their real-world goals and higher persistent usage intentions of the mobile fitness App. Underpinned by goal priming theory, we conducted two controlled experiments, surrounding core aspects of gamification narrative design, namely narrative path agility and narrative target clarity. The results, which revealed that different forms of gamification narrative design impact users' real-world fitness purpose and persistent usage intentions through different strategies, provide interesting implications for both theory and practice.